Outcome after one year of upper airway stimulation for obstructive sleep apnea in a multicenter German post‐market study. (31st May 2017) - Steffen, Armin; Sommer, J. Ulrich; Hofauer, Benedikt; Maurer, Joachim T.; Hasselbacher, Katrin; Heiser, Clemens
Abstract : Objective/Hypothesis: Upper airway stimulation (UAS) of the hypoglossal nerve has been implemented in the routine clinical practice for patients with moderate‐to‐severe obstructive sleep apnea (OSA) who could not adhere to continuous positive airway pressure. This study reports objective and patient‐reported outcome after 12 months of implantation. Study Design: Multicenter prospective single‐arm study. Methods: Consecutive patients who received the UAS system (Inspire Medical Systems, Inc., Minneapolis, Minnesota, Maple Grove, MN, U.S.A.) were enrolled in three German centers. Key study exclusion criteria included body mass index > 35 kg/m 2, apnea–hypopnea index (AHI) < 15 or > 65, or complete concentric collapse at the soft palate during sedated endoscopy. Data collection at 6‐ and 12‐month visit include home sleep test and patient‐reported outcome measures. Results: Among the total of 60 participants, the median AHI reduced from 28.6 to 9.5 from baseline to 12 months. Patient‐reported outcome measured in Epworth Sleepiness Scale and Functional Outcomes of Sleep Questionnaire both improved significantly from baseline to 12 months. The average usage time was 39.1 ± 14.9 hours per week among all participants based on recordings by the implanted device. One patient requested a removal of the device for cosmetic and other personal reasons and was completed without sequelae. Conclusion: This study supported that UAS is a safe and effective treatment option for patients with OSA in routine clinical practice. Level of Evidence: 4. Laryngoscope, 128:509–515, 2018